2017
DOI: 10.1007/s11548-017-1665-7
|View full text |Cite
|
Sign up to set email alerts
|

Mixed reality ultrasound guidance system: a case study in system development and a cautionary tale

Abstract: We recommend a wary eye in development of mixed reality ultrasound image guidance systems emphasizing small-scale iterative evaluation alongside system development. Ultimately, we recommend that the image-guided intervention community furthers and deepens this discussion into best practices in developing image-guided interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Also, the resolution is very low (1268 × 720) and the integration of artificial intelligence does not make any difference. References 39,41,43,44,47,48,79,and 86‐89 used different screens, PCs, or monitors to view the data along with other devices like iPad, projectors, and camera. Different from all these, Zhao et al 9 used a glasses‐free polyhedron‐shaped display device for telesurgical guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the resolution is very low (1268 × 720) and the integration of artificial intelligence does not make any difference. References 39,41,43,44,47,48,79,and 86‐89 used different screens, PCs, or monitors to view the data along with other devices like iPad, projectors, and camera. Different from all these, Zhao et al 9 used a glasses‐free polyhedron‐shaped display device for telesurgical guidance.…”
Section: Discussionmentioning
confidence: 99%
“…In this article [13], the use of mixed reality for the development of an Augmented Paper Map (APM) system was observed, the two authors who developed this article report Scrum, as the methodology that helped them to achieve the objectives of their article, explaining a bit about the roles and artifacts that were useful for the application of this methodology, they also express the design philosophy they used, which is that the design is user-centered, so that in this way the final product complies with the needs of these (Users), and thus achieve the greatest satisfaction with the minimum effort on the part of the user. It also tells us about the activities that they had to develop and carry out during the course of the article, as well as the exploration, analysis and evaluations that they had to develop for the development of the Augmented Paper Map (APM) system.…”
Section: B Related Workmentioning
confidence: 97%
“…Previous studies showed that the fidelity of a VR system is associated with the number of sensory modalities it stimulates [7]. For instances, many studies have demonstrated that multimodal sensory cues-haptic, auditory, and visual (HAV)-enhances experience, motor skill performance, and learning of the VR users [8], [9], [10] compared to bimodal (audio and visual-AV) or unimodal VR system and is as effective as live training for motor skill learning [11], [12]. Nevertheless, simulating haptic interactions is challenging.…”
Section: Introductionmentioning
confidence: 99%